Temporal control of epigenetic centromere specification - Valente, Luis P (2016)
All living organisms require accurate mechanisms to faithfully inherit their genetic material during cell division. The centromere is a unique locus on each chromosome that supports a multiprotein structure called the kinetochore. During mitosis, the kinetochore is responsible for connecting chromosomes to spindle microtubules, allowing faithful segregation of the duplicated genome. In most organisms, centromere position and function is not defined by the local DNA sequence context but rather by an epigenetic chromatin-based mechanism. Centromere protein A (CENP-A) is central to this process, as chromatin assembled from this histone H3 variant is essential for assembly of the centromere complex, as well as for its epigenetic maintenance. As a major determinant of centromere function, CENP-A assembly requires tight control, both in its specificity for the centromere and in timing of assembly. In the last few years, there have been several new insights into the molecular mechanism that allow this process to occur. We will review these here and discuss the general implications of the mechanism of cell cycle coupling of centromere inheritance.